If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 9) + -4 = 69 + -2x Reorder the terms: 4(9 + x) + -4 = 69 + -2x (9 * 4 + x * 4) + -4 = 69 + -2x (36 + 4x) + -4 = 69 + -2x Reorder the terms: 36 + -4 + 4x = 69 + -2x Combine like terms: 36 + -4 = 32 32 + 4x = 69 + -2x Solving 32 + 4x = 69 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 32 + 4x + 2x = 69 + -2x + 2x Combine like terms: 4x + 2x = 6x 32 + 6x = 69 + -2x + 2x Combine like terms: -2x + 2x = 0 32 + 6x = 69 + 0 32 + 6x = 69 Add '-32' to each side of the equation. 32 + -32 + 6x = 69 + -32 Combine like terms: 32 + -32 = 0 0 + 6x = 69 + -32 6x = 69 + -32 Combine like terms: 69 + -32 = 37 6x = 37 Divide each side by '6'. x = 6.166666667 Simplifying x = 6.166666667
| 3x+2(3x)-10=16 | | 88=8(t+4) | | -3w^2+11w-6=0 | | 1.50h+4.25=11.75 | | 25a+10b+5c= | | n(n+1)(2+n)=84 | | 5(x+9)-14=4x | | 0+3y=15 | | 0.05x=4.25 | | (4-x)/2=(6+x)/5 | | 475+.15m=487 | | 3(-2)+4y=10 | | 4(-1w+4)=3(2w+2) | | 23(4.69)+0.5(-9.8)(4.69)=y | | h=-16t^2+1500 | | (2x-4)/5=3x/3 | | 4X^2+y^2+8X-4y-92=0 | | -4t+14t=3(2t+9)-3 | | -2-3x-2=-2x+8-2x | | 80-3r=5r-80 | | -4t+14t=3(2t+0)-3 | | -3v-4v+4=0 | | m(mx-3)-16x=-12 | | 4(x+1.25)-6=x-1 | | 24+.99m=1.49m | | 35=22x-12+5 | | 3x-5(2)=-9 | | 21x^2-32x+12=0 | | 5x+2y+12x-3=180 | | 5m^2+2m=11 | | 3x-5x+7+5x=2x+4x-6 | | 3-4x=7-6x |